PENGUATAN KARAKTER PEDULI LINGKUNGAN DI LINGKUNGAN MADRASAH IBTIDAIYAH AL-MURSYIDAH JONGGRONG MELALUI PROGRAM ADIWIYATA - Ivo Retna Wardani; Yeni Fitriya; Rohmad Rohmad (AFHAM : Jurnal Pendidikan dan Keguruan, 2026)
Strengthening students' environmentally conscious character within the madrasah (Islamic school) environment is implemented as part of the Adiwiyata program. This program aims to foster a sense of responsibility among the school community regarding environmental protection and management; consequently, it requires careful planning, a structured process for character reinforcement, and an analysis of supporting and inhibiting factors. This study employs a descriptive qualitative research method, with data collected through documentation, observation, and interviews. Data analysis was conducted using triangulation. The results indicate that: (1) activity planning involves reviewing the madrasah's vision and mission and designing environmentally oriented programs; (2) the process of strengthening environmentally conscious character is carried out by integrating environmental education into the curriculum, as well as through role modeling, habituation, and student discipline; and (3) supporting factors include stakeholder backing and well-structured activity programs, while inhibiting factors include the need for broader community support and a lack of adequate funding.